Greater operator safety with improved knapsack sprayers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Knapsack sprayers are the most commonly used equipment for pesticide application to crops in developing countries. Applicators usually spray the area ahead of themselves, which means that they then wale into the spray mist and treated foliage. Dr...